2018
DOI: 10.1038/s41598-018-35854-x
|View full text |Cite
|
Sign up to set email alerts
|

Volatilomic insight of head and neck cancer via the effects observed on saliva metabolites

Abstract: Head and neck cancer (HNC) is a heterogeneous malignant disease with distinct global distribution. Metabolic adaptations of HNC are significantly gaining clinical interests nowadays. Here, we investigated effects of HNC on differential expression of volatile metabolites in human saliva. We applied headspace solid phase microextraction coupled with gas chromatography-mass spectrometry analysis of saliva samples collected from 59 human subjects (HNC − 32, Control − 27). We identified and quantified 48 volatile o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…This decrease of undecane is in contrast to an increase found in breath in HNSCC ( 40 ) and patients with PTC ( 46 ). Furthermore, saliva analysis of the single VOCs 1,4-dichlorobenzene, 1,2-decanediol, 2,5-bis1,1-dimethylethylphenol, and E-3-decen-2-ol allowed to discriminate HNSCC patients from controls with a sensitivity and specificity between 80–100% and 80–100%, respectively ( 51 ), again being different to VOCs found in exhaled breath and urine ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…This decrease of undecane is in contrast to an increase found in breath in HNSCC ( 40 ) and patients with PTC ( 46 ). Furthermore, saliva analysis of the single VOCs 1,4-dichlorobenzene, 1,2-decanediol, 2,5-bis1,1-dimethylethylphenol, and E-3-decen-2-ol allowed to discriminate HNSCC patients from controls with a sensitivity and specificity between 80–100% and 80–100%, respectively ( 51 ), again being different to VOCs found in exhaled breath and urine ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…Taware et al applied the same principle to oral cancer and analysed the salivary volatile composition of a small cohort of 32 oral cancer patients and 27 controls. The authors reported that the volatiles 1,4-dichlorobenzene, 1,2-decanediol, 2,5-bis1,1-dimethylethylphenol and E-3-decen-2-ol were significantly associated with the malignant disease, possessing an excellent discriminatory potential [87].…”
Section: Salivary Volatomicsmentioning
confidence: 99%
“…As the name suggests, in this methodology the volatile metabolites are loaded in the GC column and the separated metabolites then detected by MS. The sample volatiles can be preconcentrated using various approaches such as Solid Phase Micro Extraction (SPME) or Needle Trap Micro Extraction (NTME), desorbed in the GC, separated and detected [87,95,97]. The samples that are not volatile under normal conditions can be derivatized to make the metabolites thermostable and gaseous at higher temperature.…”
Section: Gc-msmentioning
confidence: 99%
“…Omics-based approaches have been significantly improved recently with the addition of novel concepts such as exposome/exposomics, the study of the environmental exposure, to unravel the role of the environment in human diseases. Furthermore, the addition of adductomics, the study of compounds that bind DNA and cause damage and mutations, and volatilomics, the study of volatile organic compounds to the metabolomics/lipidomics analysis for comprehensive research of the metabolome have been newly emerging [2,10,11]. Exposome is a person's total lifestyle and environmental exposures, which is not well understood yet.…”
Section: Application Field Of Omics Technology In Molecular Medicinementioning
confidence: 99%